Applied Research of Water Jet Technology in Preventing Rock Burst Occurred in Roadways. (4th May 2022) - Yang, Zeng-qiang; Xiao, Cang-yan; Li, Chang-hao; Ren, Chang-le
Abstract : Taking mining area 2502 in the Huayan mine field which was affected by strong geological tectonic stress as an engineering background, the water jet technology is studied through in-site survey, laboratory test, theoretical analysis, numerical simulation, and field industrial test. The research results are as follows: the burst tendency of No. 5 coal seam can be reduced to a certain extent after softening with water, and then the water jet technology is used to prevent rock burst of roadways; the typical characteristics of rock-burst accidents mainly cause heaving floor and serious deformation of two sides. The occurrence mechanism of rock burst in roadway ribs has two different forms, and they are static load dominant type and dynamic load dominant type. The abutment stress concentration value is higher than a certain concentration static load, it will affect the coal and rock medium in the floor, and the coal and rock medium in the floor will be transformed into a plastic state and then occur rock burst; the water jet technology for roadway ribs can effectively prevent rock burst of roadway ribs and floor based on the dynamic and static loads superposition theory and Terzaghi theory. Based on the results of numerical simulation, the specific parameters of water jet technology for roadway ribs in 250204 tailgate are as follows: the diameter and length of initial borehole are 110 mm and 20.0 m, the diameter and length of water jet section are 500 mm and 15.0 m, and the spacing between adjacent water jet boreholes is 3.0 m; the monitoring result of signal intensity by EMR indicates that the decreasing amplitude of signal intensity of EMR is about 60.2% on the side of coal-pillar rib, and the decreasing amplitude of signal intensity of EMR is about 68.6% on the side of solid-coal rib; the convergences monitoring result indicates that the convergence ratio of roadway height is about 3.2%, and the convergence ratio of roadway width is about 2.3% in the pressure relief roadway part; the water jet technology is not only helpful to the prevention of rock burst for the roadway ribs but also can play a good prevention of rock burst for roadway floor. The research results provide a theoretical foundation and a new guidance for preventing rock burst in roadway ribs and floor with similar engineering geological conditions.